MORTUARY RITUALS AND CRANIAL MODIFICATIONS AT CEIBAL: FROM THE EARLY MIDDLE PRECLASSIC TO THE TERMINAL CLASSIC PERIOD. Issue 1 (31st May 2017) - Palomo, Juan Manuel; Inomata, Takeshi; Triadan, Daniela
Abstract: Skeletal remains excavated from the lowland Maya site of Ceibal, representing approximately 117 individuals, provide significant data for the study of changes in bodily treatments and mortuary practices from 1000b.c. toa.d. 900. The early Middle Preclassic residents of Ceibal apparently did not bury their dead inside residential structures, which represents a burial practice different from those found at contemporaneous Belizean sites. During this time, tabular erect cranial deformations were found among possible local residents. Sacrificial burials were present by the end of this period, but skeletal remains of violent rituals deposited in public spaces increased from the Middle Preclassic to the Late Preclassic. During the Late Preclassic, tabular erect cranial deformations coexisted with tabular oblique shapes. The Classic period witnessed a prevalence of tabular oblique forms, which were probably tied to local residents. The common placement of the dead under house floors and the preference of ceramic vessels as burial goods also indicate Ceibal's strong affinities with other parts of the Maya lowlands during the Late Classic period. During the Terminal Classic period, there was a resurgence in the placement of sacrificial burials in public spaces and tabular erect cranial deformations were found in possible non-local individuals.